2015
DOI: 10.1039/c5ce00543d
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary growth of microscale single crystalline GaN on an amorphous layer by the combination of MBE and MOCVD

Abstract: To integrate multiple functional devices on a chip, advances in epitaxial growth on heterosubstances are required. As one approach to achieve an epitaxial layer on an amorphous substrate, we developed a method of combined epitaxial growth using molecular beam epitaxy (MBE) and metal-organic chemical vapor deposition (MOCVD). This two-stage combined growth can be used to grow a binary gallium nitride (GaN) on any thermally durable substances. The first MBE growth step provided us effective nucleation with unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…5c. However, we have observed that the crystallinity of the buffer GaN becomes worse as the growth temperature is abruptly increased in the MOCVD system due to thermal re-crystallisation27. On the other hand, GaN NRs stood out as zone II grain features in the SZM with strong selective orientation since both the surface and bulk diffusion are significantly active at such a high homogenous temperature of ~0.535.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…5c. However, we have observed that the crystallinity of the buffer GaN becomes worse as the growth temperature is abruptly increased in the MOCVD system due to thermal re-crystallisation27. On the other hand, GaN NRs stood out as zone II grain features in the SZM with strong selective orientation since both the surface and bulk diffusion are significantly active at such a high homogenous temperature of ~0.535.…”
Section: Resultsmentioning
confidence: 90%
“…5d tended to grow along the surfaces of the wetting layers. Previously, we had related the initial nucleation mechanism on the amorphous layer to Ga 2 O 3 nanoclusters27. Similar growth behaviours might be induced at the interface of the GaN buffer and quartz substrates, as we used the same epitaxy system and substrates.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations